Perancangan Sistem Kehadiran Berbasis Website Dengan Integrasi Geolokasi Untuk Karyawan MI Al- Amin Menggunakan Metode Agile - Fatahillah Arinal; Rinci Kembang Hapsari (Institut Teknologi Adhi Tama Surabaya, 2025)
This study develops a website-based attendance system with geolocation integration for MI Al-Amin employees using the Agile method. The system aims to replace manual attendance, which often leads to fraud and inefficiency. The development process involves the Agile model, which includes timebox planning, daily stand-up meetings, demonstrations, and retrospective meetings. Needs analysis was carried out through interviews, the system was designed using UML, and it was implemented as a web application that supports location-based attendance, employee management, leave management, and attendance reporting. Unit testing, integration testing, system testing, and user acceptance testing confirm that the application meets user needs, with black-box testing used throughout the process. System quality evaluation follows the ISO 9126 standard, focusing on reliability, accessibility, security, and usability. A total of 28 respondents assessed the system using a Likert scale, resulting in an average score of 82.14%, categorized as satisfactory. These results indicate that the attendance system is feasible for use, although it still requires enhancements to security and user interface comfort.